ASME 2012 International Manufacturing Science and Engineering Conference 2012
DOI: 10.1115/msec2012-7203
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Machinability of PA-6/nano-CaCO3 Composite

Abstract: Nowadays, polymer nano-composites have attracted manufacturers’ attention because of good mechanical, thermal, and physical properties. During the past decade, the requirement of the direct machining of polymer nano-composites increases because most of the polymer nano-composites were produced by extrusion method in simple cross section shapes and request for personalized products increases. In this study, the effect of milling parameters (spindle speed and feed per tooth) and nano-CaCO3 content on the machina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The levels of milling parameters and MWCNTs' content include spindle speed (600, 1,400, 2,200, and 3,000 rpm), feed (0.1, 0.15, 0.2, and 0.25 mm/tooth), and MWCNTs' content (0 and 3.5 wt %). Depth of cut was considered constant due to its negligible effect reported by Farshbaf et al [7].…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of milling parameters and MWCNTs' content include spindle speed (600, 1,400, 2,200, and 3,000 rpm), feed (0.1, 0.15, 0.2, and 0.25 mm/tooth), and MWCNTs' content (0 and 3.5 wt %). Depth of cut was considered constant due to its negligible effect reported by Farshbaf et al [7].…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…On the other hand, it has been proven that the particles of MWCNT can act as a lubricant to reduce the friction [18]. Thus, it can be concluded that the MWCNT particles act as a lubricant in the cutting area and reduce the friction between tool/workpiece and tool/chip [7]. Thus, the possibility of seizing chip to the tool tip reduces and results in lesser BUE and better surface finish.…”
Section: Repeating Steps 3 and 4 Until The Termination Criterion Is Smentioning
confidence: 99%
See 1 more Smart Citation
“…We established that the mass flow rate for the organobentonite-filled nylon is significantly lower, while the modification has also a positive effect on other physical characteristics of the material. Several descriptions of the influence of organobentonite clay on the mechanical properties of nylon 6 can be found in the literature [21,22], or other nano-fillers (nano-CaCO 3 ) on the milling properties of polyamide [23], but there is no information on how it affects the laser machining of these composites.…”
Section: Introductionmentioning
confidence: 99%